ANALYSIS OF LAND SUITABILITY FOR ROBUSTA COFFEE CULTIVATION (Coffea canephora) IN BENTENGE VILLAGE, MALLAWA DISTRICT, MAROS DISTRICT - Hadija, Hadija; Haerul, Haerul; Nurjaya, Muhammad; Azisah, Azisah (Jurnal Agrotek Tropika, 2025)
The ability of land with different properties, regional characteristics, and soil nutrient status to affect the productivity of coffee plants is affected, so it is important to evaluate regional characteristics and soil nutrient status so that the land suitability class for coffee plant cultivation can be known. The purpose of this study was to provide information on the extent of the level of land and climate suitability of Bentenge Village, Mallawa Subdistrict, for robusta coffee cultivation. The research was conducted from September to December 2022 in Bentenge Village, Malawa District, Maros Regency, which has been cultivating coffee, especially robusta coffee, for decades. This research method uses a survey approach and laboratory analysis, whose results are interpreted into a land suitability map. Furthermore, data on regional conditions and nutrient status in Bentenge Village were juxtaposed with good coffee cultivation guidelines in MOA No. 49 of 2014 to determine the level of land suitability for robusta coffee cultivation. The results showed that the land in Bentenge Village, Mallawa Sub-district, is suitable (S2) to marginally suitable (S3) for the development of robusta coffee cultivation..